The Effectiveness of Competence-Based Training Program in the Technical Implementation Unit (UPT) of Job Training Center Pasuruan - Rossa Silfiah; Imarotus Shohiya Multazima (Brawijaya University, 2022)
In the free labor market, workers are required to have adequate skills in a particular field so that they can be applied in their work. UPT Job Training Center Pasuruan is one of the public organizations or government agencies under the auspices of the Department of Manpower and Transmigration of East Java Province. Its mission is to improve the competence of the workforce and establish partnerships in order to meet the needs of the labor market. The existing data show that the absorption of labor has not been optimal. So, it is necessary to know whether or not the implementation of the program is effective. The methods for data collection were qualitative research methods. With qualitative method, it is stated how effective the implementation of competency-based training programs is and what are the supporting and inhibiting factors in the process of implementing competency-based training programs at UPT Job Training Center Pasuruan. Data were collected through observation, interviews, and documentation. The effectiveness implementation of training program is measured using three variables according to Sandfort and Moulton (2015); (1) the context which can influence change, (2) open priority programs, (3) face technical and adaptive challenges to create change, applying analytical inquiry and social skills. The inhibiting factors for the program were found to be different types of participants, participants educational background, trainer skills in training participants with disabilities, changes in budget or training packages. The solution to these obstacles requires creativity in applying the supporting factors are resources (human resources, financial resources, facilities and infrastructure), and cultural values.